2022
DOI: 10.1111/cns.13990
|View full text |Cite
|
Sign up to set email alerts
|

Gut bacterial profiles in Parkinson's disease: A systematic review

Abstract: Introduction:Recent advances have highlighted the relationships between gut dysbiosis and Parkinson's disease (PD). Microbiota transplantation from PD patients to mice can induce increased alpha-synuclein-mediated motor deficits. Human studies have identified differences in the gut microbiota of PD patients compared to healthy controls. We undertook a systematic review to evaluate the available evidence for the involvement of gut bacteria in the etiology of PD. Methods:The PubMed databank, the China National K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 92 publications
0
36
0
1
Order By: Relevance
“…Environmental and social factors may also influence risk for stroke, with recognition of the impact of commensal microorganisms on health and disease. 59,60 Emerging gut-brain-microbiome research using murine models, humanized mouse models, and human clinical trials 61,62 has shown that microbiome-related metabolic changes can be induced by stress, 63 exercise, 64 and even changes in the circadian rhythm. These alterations in metabolite composition have been shown across different brain regions, peripheral organs, and in circulation.…”
Section: Association Of Gut Microbiota With Circulating Metabolitesmentioning
confidence: 99%
“…Environmental and social factors may also influence risk for stroke, with recognition of the impact of commensal microorganisms on health and disease. 59,60 Emerging gut-brain-microbiome research using murine models, humanized mouse models, and human clinical trials 61,62 has shown that microbiome-related metabolic changes can be induced by stress, 63 exercise, 64 and even changes in the circadian rhythm. These alterations in metabolite composition have been shown across different brain regions, peripheral organs, and in circulation.…”
Section: Association Of Gut Microbiota With Circulating Metabolitesmentioning
confidence: 99%
“…A previous review showed results similar to the current study, expressed as the higher abundance of Verrucomicrobiaceae, Christensenellaceae and Bifidobacteriaceae in PD subjects compared with controls. 55 In addition, it was reported that the abundance of Prevotellaceae is lower in PD subjects compared with controls. While the mentioned review showed different results regarding Ruminococcaceae which have been reported to be highly abundant in PD subjects in 3 studies, 55 in the current research, 10 studies have been selected and analyzed to reflect the conclusion of a non-significant difference between PD and controls.…”
Section: Discussionmentioning
confidence: 99%
“…55 In addition, it was reported that the abundance of Prevotellaceae is lower in PD subjects compared with controls. While the mentioned review showed different results regarding Ruminococcaceae which have been reported to be highly abundant in PD subjects in 3 studies, 55 in the current research, 10 studies have been selected and analyzed to reflect the conclusion of a non-significant difference between PD and controls. Another study by Romano et al showed the results similar to the current studies regarding the abundance of Bifidobacteriaceae, Lachnospiraceae and Faecalibacterium in PD subjects compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by more than 15 cohort studies which found correlations between neurological deterioration and gut dysbiosis characterised by reduced Prevotella, lower levels of faecal short-chain fatty acids (SCFAs), increased lipopolysaccharide-(LPS) producing bacteria, and increased proinflammatory Lactobacillaceae (Li et al, 2023). Murine models have built on this concept.…”
Section: Intestinal Phenotype Hypothesismentioning
confidence: 94%